PENGARUH BRAND AMBASSADOR RED VELVET DALAM IKLAN “MY BEAUTY MY RULE” TERHADAP BRAND IMAGE AZARINE COSMETIC (Survei Pada Followers Instagram @azarinecosmeticofficial) - Sagita, Selvi; Sari, Wina Puspita; Fatimah, Anggun Nadia (PRoMEDIA, 2024)
Advertising is an effective and efficient marketing strategy. Companies often use public figures or celebrities as brand ambassadors to make their advertisements more engaging. The existence of brand ambassadors also contributes to a strong public perception of the brand. The aims of this research is to determine the influence of Red Velvet as brand ambassadors in in the "My Beauty My Rule" advertisement campaign on the brand image of Azarine Cosmetic. This study uses the VisCAP theory popularized by Rossiter and Percy. This research uses a survey method with an explanatory quantitative. Data collection technique utilized a questionnaire distributed to 100 respondents who are followers of Instagram @azarinecosmeticofficial through Google Forms. The data analysis technique utilized in this research is included the normality test, linearity test, correlation test, simple linear regression analysis, determination coefficient test, and hypothesis test (t test), all performed with SPSS 25 for Windows. The test results indicate that the brand ambassador Red Velvet in the "My Beauty My Rule" advertisement has an influence of 43.4% on the brand image of Azarine. There are other variables not included in this study that affect the brand image of Azarine Cosmetic by 56.6%.  Keywords: Brand Ambassador, Brand Image, Advertisement, Cosmetics, K-pop